2009
DOI: 10.1111/j.1365-2044.2009.06017.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the i‐gel™ with the LMA‐Unique™ in non‐paralysed anaesthetised adult patients

Abstract: SummaryThis study assessed two disposable devices; the newly developed supraglottic airway device i-gel TM and the LMA-Unique TM in routine clinical practice. Eighty patients (ASA 1-3) undergoing minor routine gynaecologic surgery were randomly allocated to have an i-gel (n = 40) or LMA-Unique (n = 40) inserted. Oxygen saturation, end-tidal carbon dioxide, tidal volume and peak airway pressure were recorded, as well as time of insertion, airway leak pressure, postoperative sore-throat, dysphonia and dysphagia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
62
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 37 publications
18
62
1
3
Order By: Relevance
“…The i-gel has been studied and shown to have high insertion success rate and low device failures under both spontaneous and controlled ventilation (7,(14)(15)(16)(17). Various studies have reported a median insertion time for the i-gel ranging from 5 to 15 sec (14,16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The i-gel has been studied and shown to have high insertion success rate and low device failures under both spontaneous and controlled ventilation (7,(14)(15)(16)(17). Various studies have reported a median insertion time for the i-gel ranging from 5 to 15 sec (14,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported a median insertion time for the i-gel ranging from 5 to 15 sec (14,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…First time success rates for the i-gel TM found in our study was 85.6% which is lower than the results published in recent cohorts. The i-gel was inserted in several studies on the first attempt in more than 90% of patients 1,2,[13][14][15] . This finding could have been caused by an initial relative lack of experience in some operators.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…These studies showed that the leak pressures were higher with I-gel than with the other airway devices [14,15,16]. Not only the insertion times were lower but also the ease of insertion of the I-gel was better than those of the LMA-Unique in lean patients [14,16].…”
Section: Discussionmentioning
confidence: 97%